2016
DOI: 10.1016/j.stemcr.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Oncometabolic Nuclear Reprogramming of Cancer Stemness

Abstract: SummaryBy impairing histone demethylation and locking cells into a reprogramming-prone state, oncometabolites can partially mimic the process of induced pluripotent stem cell generation. Using a systems biology approach, combining mathematical modeling, computation, and proof-of-concept studies with live cells, we found that an oncometabolite-driven pathological version of nuclear reprogramming increases the speed and efficiency of dedifferentiating committed epithelial cells into stem-like states with only a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…Recently studies have demonstrated that a subpopulation of cancer cells, often referred to as cancer stem cells (CSCs) or tumor initiating cells (TICs) [5], is capable of extensive proliferation, self-renewal, and increased frequency of tumor initiation [6]. Gastric CSCs can be enriched with several defined markers, including CD44, aldehyde dehydrogenase (ALDH), and Lgr5 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Recently studies have demonstrated that a subpopulation of cancer cells, often referred to as cancer stem cells (CSCs) or tumor initiating cells (TICs) [5], is capable of extensive proliferation, self-renewal, and increased frequency of tumor initiation [6]. Gastric CSCs can be enriched with several defined markers, including CD44, aldehyde dehydrogenase (ALDH), and Lgr5 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[7][8][9][10][11] Although it remains intriguing how aging-related changes in cellular metabolism might control the layers of epigenetic instructions that influence cell fate without altering the primary DNA sequence, it should be acknowledged that the multiple processes involved in the alteration of the chromatin state, including post-translational modifications of histone proteins, incorporation of specific histone variants, methylation of DNA and ATP-dependent chromatin remodeling, are likely the pivotal molecular bridges that mediate the direct communication between the metabolic and the chromatin state, and the consequent epigenetic targeting of cell fate regulatory genes. [12][13][14][15][16][17][18][19][20] Indeed, because the usage of metabolic intermediates as substrates for chromatin-modifying enzymes provides a direct link between the metabolic state of the cell and epigenetics, one can envision that the spatio-temporal distribution of the levels and types of specific metabolites might operate as key cancer-related molecular events, rendering a cell susceptible to the epigenetic rewiring required for the acquisition of an aberrant cancer cell state and, concurrently, of refractoriness to normal differentiation.…”
mentioning
confidence: 99%
“…Such epigenetic control is often 151 related to alternative covalent modifications of histones. To address the high complexity 152 of ER, we focus on a simpler stochastic model of ER, based on that formulated 153 in [13,18] and [19]. Our model belongs to a wider class of models which consider that Evolution to the silenced state of the pluripotency-regulating gene.…”
Section: Introduction 25mentioning
confidence: 99%